Identification of an activation region in the proteasome activator REGα - Zhang, Zhiguo (The National Academy of Sciences, 1998)
Proteasomes can be markedly activated by associating with 19S regulatory complexes to form the 26S protease or by binding 11S protein complexes known as REG or PA28. Three REG subunits, α, β, and γ, have been expressed in Escherichia coli, and each recombinant protein can activate human proteasomes. Combining PCR mutagenesis with an in vitro activity assay, we have isolated and characterized 36 inactive, single-site mutants of recombinant REGα. Most are monomers that produce functional proteasome activators when mixed with REGβ subunits. Five REGα mutants that remain inactive in the mixing assay contain amino acid substitutions clustered between Arg-141 and Gly-149. The crystal structure of the REGα heptamer shows that this region forms a loop at the base of each REGα subunit. One mutation in this loop (N146Y) yields a REGα heptamer that binds the proteasome as tightly as wild-type REGα but does not activate peptide hydrolysis. Corresponding amino acid substitutions in REGβ (N135Y) and REGγ (N151Y) produce inactive proteins that also bind the proteasome and inhibit proteasome activation by their normal counterparts. Our studies clearly demonstrate that REG binding to the proteasome can be separated from activation of the enzyme. Moreover, the dominant negative REGs identified here should prove valuable for elucidating the role(s) of these proteins in antigen presentation.